Association between troponin I level and cardiovascular risk factors in asymptomatic hemodialysis patients - Shahram Taheri; Ali Asghar Pilehvarian; Nafiseh Akbari; Samane Musavi; Afsoon Emami Naeini (Wolters Kluwer Medknow Publications, 2016)
Objective: Patients on hemodialysis (HD) have a high risk for cardiovascular morbidity and mortality. Cardiac troponins are biomarkers for diagnosing acute myocardial injury or infarction. There is considerable controversy that exists in the frequency and significance of cardiac troponins in predicting cardiac injury and ischemia in HD patients. Methods: In this cross-sectional study, all HD patients more than 18-year-old, who were at least 3 months under HD, and had no sign and symptom of active cardiovascular disease (CVD), in two HD centers were enrolled. One hundred and one patients fulfilled the inclusion criteria. Blood sample for cardiac troponin I (cTnI) was drown before the initiation of HD session during their routine monthly blood testing from patients' vascular access arterial line. cTnI levels were measured by a high-sensitivity assay, VIDAS troponin I Ultra kit, and correlated with patients' demographic, clinical, and laboratory results. Findings: The patients' different demographic and clinical characteristics had no statistically significant correlation with troponin levels except for marginal trend for past medical history of diabetes and hyperlipidemia with corresponding P values of 0.072 and 0.055. Twenty-six patients had cTnI level more than 0.01 ΅g/L and only two patients had cTnI level more than 0.11 ΅g/L. For laboratory results, only fasting blood sugar had statistically significant correlation with patients' cTnI level (r = 0.357, P = 0.0001). Conclusion: Frequency of significant elevation of cTnI level in our asymptomatic HD patients was very low and if such elevation is found in this population, it may be considered as a sign of active CVD.